Estimating road vehicle speed from high-resolution satellite imagery for environmental applications: A case study of Barcelona - Annalisa Sheehan; Andrew Beddows; John Gulliver; David C. Green; Sean Beevers (Remote Sensing Applications: Society and Environment, 2025)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

New NOx and NO2 vehicle emission curves, and their implications for emissions inventories and air pollution modelling - Gregor B. Stewart; David Dajnak; Jack Davison; David C. Carslaw; Andrew V. Beddows; Napameth Phantawesak; Marc E.J. Stettler; Michael J. Hollaway; Sean D. Beevers (Urban Climate, 2024)

Measurements of particulate methanesulfonic acid above the remote Arctic Ocean using a high resolution aerosol mass spectrometer - Yangmei Zhang; Junying Sun; Xiaojing Shen; Vipul Lal Chandani; Mao Du; Congbo Song; Yuqing Dai; Guoyuan Hu; Mingxi Yang; Gavin H. Tilstone; Tom Jordan; Giorgio Dall’Olmo; et al. (Atmospheric Environment, 2024)

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Measurement of road traffic brake and tyre dust emissions using both particle composition and size distribution data - David C.S. Beddows; Roy M. Harrison; Tomasz Gonet; Barbara A. Maher; Nicholas Odling (Environmental Pollution, 2023)

Detecting high emitting vehicle subsets using emission remote sensing systems - Omid Ghaffarpasand; Karl Ropkins; David C.S. Beddows; Francis D. Pope (Science of The Total Environment, 2023)

Sea Ice Microbiota in the Antarctic Peninsula Modulates Cloud-Relevant Sea Spray Aerosol Production - Manuel Dall’Osto; Dolors Vaqué; Ana Sotomayor-Garcia; Miguel Cabrera-Brufau; Marta Estrada; Teresa Buchaca; Montserrat Soler; Sdena Nunes; Sebastian Zeppenfeld; Manuela van Pinxteren; Hartmut Herrmann; Heike Wex; et al. (Frontiers in Marine Science, 2022)
Sea spray aerosol (SSA) formation plays a major role in the climate system. The Antarctic Peninsula (AP) is affected by the greatest warming occurring in the Southern Ocean; changes in cryospheric and biological processes are being observed. Whilst there is some evidence that organic material produced by ice algae and/or phytoplankton in the high Arctic contributes to SSA, less is known about Antarctic Sea ice (sympagic) regions. To gain insight into the influence of Antarctic Sea ice biology and biogeochemistry on atmospheric aerosol, we report simultaneous water-air measurements made by means of in situ aerosol chamber experiments. For the first time, we present a methodology showing that the controlled plunging jet aerosol chamber settings do not cause major cell disruption on the studied sea ice ecosystems. Larger sea ice phytoplankton cells (>20 µm; mainly diatoms) tend to sediment at the bottom of the chamber (during the 24h experiment) and likely have a minor role on SSA production. When comparing four chamber experiments - we find that the two producing more SSA are the ones with highest abundance of nanophytoplankton cells (<20 µm; mainly nanoflagellates) as well as viruses. Our marine biogeochemical data show two broad groups of dissolved organic carbon: one rich in carbohydrates and proteic material and one rich in humic-like substances; the latter enhancing SSA production. This work provides unique insights into sea ice productivity that modulates SSA production, with potentially significant climate impacts. Further studies of these types are advised in order to see how microbiology impacts the biogeochemical cycling of elements and how aerosols are formed and processed in cold regions.